Physiological and genetic analyses of post-anthesis heat tolerance in winter wheat (Triticum aestivum L.) - Vijayalakshmi, Kolluru (Kansas State University, 2007)
Post-anthesis high temperature stress in wheat (Triticum aestivum L.) is a major cause of yield reduction. This process results in the loss of viable leaf area and a decrease in green leaf duration ultimately causing a yield loss. The objectives of this study were to (i) phenotype a recombinant inbred line population for heat tolerance traits, (ii) understand the genetic basis of heat tolerance by mapping quantitative trait loci (QTL) linked to yield-related traits under high temperature, (iii) model stay-green under high temperature stress and map the QTL linked to stay-green parameters, and (iv) validate the markers linked to QTL under field conditions. A filial6:7 (F6:7) recombinant inbred line (RIL) population was developed by crossing Ventnor, a heat-tolerant white winter wheat with Karl 92, a relatively heat susceptible hard red winter wheat. From 10 DAA to maturity, the treatments of optimum temperature or high temperature stress (30/25°C) were imposed on the RILs. The traits measured included grain filling duration (GFD), kernels per spike, thousand kernel weight (TKW), and grain filling rate (GFR). The stay-green traits calculated were: i) time between 75% and 25% green, ii) maximum rate of senescence, iii) time to maximum rate of senescence, and v) percent green at maximum senescence. Genetic characterization was performed using microsatellite (SSR), amplified fragment length polymorphism (AFLP) and a sequence tag site (STS) markers. GFD was positively correlated with TKW and negatively with GFR and maximum rate of senescence. Principle component analysis (PCA) showed kernels per spike, maximum rate of senescence, and TKW accounted for 98% of total variability among the genotypes for heat tolerance. The most significant QTL for yield traits co-localized with marker Xgwm296 for TKW, Xgwm356 for kernels per spike, and Xksum61 for GFR. The QTL for stay-green traits co-localized with markers P41/M62-107 on Chromosome 2A, Xbarc136 on Chromosome 2D, P58/MC84-146 on Chromosome 3B, P58/M77-343 on Chromosome 6A, and. P58/MC84-406 on Chromosome 6B. These results indicate that increased green leaf area duration has a positive effect on the grain yield under high temperature. Once the kernels per spike are established, GFD and TKW can be used as selection criteria for post-anthesis heat-tolerance.
Keywords: Heat Tolerance; Wheat; QTL mapping; Senescence; Grain-fill stress; Marker assisted selection; Agriculture, Agronomy (0285); Agriculture, General (0473); Biology, Biostatistics (0308); Biology, General (0306); Biology, Genetics (0369); Biology, Molecular (0307); Biology, Plant Physiology (0817)